Computational Science of Vapor Liquid Two Phase Flow Inside Heat Exchanger Tube - Malhotra, Sandeep (International Journal of Computer Sciences and Engineering, 2025)
A heat exchanger is one of the key components in air-conditioning and refrigeration systems. Condensers and evaporators are typically heat exchangers which are used to condense vapors into liquid and evaporate liquid into vapor respectively also known as phase transition. To obtain the dynamic performance of the heat exchanger system, simulation in transient state is required. For prediction of such performance a homogeneous vapor liquid two phase flow model is used. To obtain the solution of the model science of the computations need to be used efficiently. In the present paper an efficient computational model and method are proposed. The method is capable of predicting the refrigerant temperature distribution, velocity of refrigerant, tube wall temperature as a function of position and time. A single tube heat exchanger with refrigerant R22 as working fluid was chosen as a sample and some tests were carried out to determine its transient response. The examination of results indicates that the computational model provides a reasonable prediction of dynamic response.